L-ascorbic acid release from polymeric matrixes based on blends of chitosan, collagen and hyaluronic acid. (21st November 2016) - Kaczmarek, B.; Sionkowska, A.; Markiewicz, E.
ABSTRACT: 3D porous composites based on blends of chitosan, collagen and hyaluronic acid were obtained. L-ascorbic acid was incorporated into the composites. The structure of composites was studied by IR spectroscopy and SEM. Moreover, mechanical properties, porosity and density of the blends were studied. The release of L-ascorbic acid from biopolymeric matrixes was studied by UV-Vis spectroscopy. The results showed that biopolymeric matrixes based on the blends of chitosan, collagen and hyaluronic acid can be used as 3D systems for L-ascorbic acid delivery. The addition of hyaluronic acid to chitosan/collagen blends leads to the decrease of amount of released agent.